Approximate solutions for MHD squeezing fluid flow by a novel method - İnç, Mustafa; Akgul, Ali (Springer International Publishing Ag, 2014)
In this paper, a steady axisymmetric MHD flow of two-dimensional incompressible fluids has been investigated. The reproducing kernel Hilbert space method (RKHSM) has been implemented to obtain a solution of the reduced fourth-order nonlinear boundary value problem. Numerical results have been compared with the results obtained by the Runge-Kutta method (RK-4) and optimal homotopy asymptotic method (OHAM).
Keywords: reproducing kernel method; series solutions; squeezing fluid flow; magnetohydrodynamics; reproducing kernel space